RFID based computer security system / Imran Syauqi Abdul Rahman - Abdul Rahman, Imran Syauqi (2024)
In our daily lives, Radio Frequency Identification (RFID) has been used unintentionally when we use public transit, board airplanes with our passports, make purchases in stores, and pay tolls on motorways. These capabilities make it possible for users to access laptops and desktop computers using this technology. This is due to the fact that, like everyone else, we humans occasionally forget our own passwords for accounts on websites like Facebook, Google, and Windows. It is shown that users no longer need to memorize their laptop or computer's password to log into the Windows operating system, proving that technology is meant to make people's lives easier. An Arduino Uno and an RC-522 module can be used as microcontrollers to build a project that lets users access their computers without entering their passwords. However, to create such a programme, one must first understand and comprehend the C language that the microcontroller uses. This project's goals are to provide a different technique for users to log onto computers, to make computers easier for users to access with an RFID system, and to find easy ways to access Windows devices.